CRISIS COMMUNICATION EFFECTIVENESS IN DISASTER MANAGEMENT: CASE STUDIES AND LESSONS - Sidderatul Akbar; Silvia Ekasari; Farida Asy'ari (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2025)
Crisis communication is a key component of effective disaster management. This research reviews the literature related to crisis communication strategies and evaluates case studies of crisis communication in various disaster contexts. Based on the literature review, it was found that responsiveness, information accuracy, and appropriate choice of communication channels are the main pillars that support communication effectiveness in emergency situations. The application of information and communication technology, including social media, is now an integral part of delivering early warnings and evacuation instructions to the public. The analysis shows that the speed of early warning and post-disaster information delivery has a major impact on mitigating losses and accelerating the recovery process. Clarity, consistency and transparency of messages are known to increase public trust, encourage compliance with emergency instructions and reduce the risk of misinformation spreading. Two-way communication, which allows for community feedback, also plays an important role in evaluating and improving disaster management resources. Lessons learned from the case analysis show the importance of building communication capacity before a disaster strikes to improve community preparedness. Proactive education and training programs can help build community resilience before a disaster, as well as enable more informed decision-making when a crisis occurs. Such initiatives make crisis communication not only a reactive measure but also part of sustainable disaster mitigation efforts. This research provides recommendations for the development of a more integrated crisis communication strategy, adapting to the latest developments in informative technology, which is expected to strengthen disaster management in the future.